Implementation of Green Banking at BSI in Realizing Sustainable Development Goals (SDGs) - Nabila Achmad; Muhtadin Amri (Universitas Islam Negeri (UIN) Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: This study aims to analyze the extent to which BSI has implemented green banking indicators in its operational activities, and what are the challenges and opportunities faced by BSI during the implementation of green banking. Research Methods: The research method used is a qualitative approach with a document study research type. The data used are sourced from BSI's sustainability report and other sources such as books, journals, scientific articles, modules, and websites. Results: BSI has implemented green banking in accordance with the green banking indicators, namely carbon emissions, green building, green reward, reuse/recycle/refurbish, paperless, and green investment. In addition, BSI also implements green banking in accordance with the Sustainable Development Goals (SDGs), and maqashid sharia. Conclusion: BSI not only implements green banking technically, but also implements the values of maqashid sharia in maintaining environmental sustainability as part of the mission of sharia banking.